THE STUDENTS’ PROBLEMS IN SPEAKING AT MTS NURUSSA’ADAH TELUK RENDAH TEBO ILIR - FAJRI, ANIL (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2024)
This research focused on describing students' speaking problems, employing the descriptive qualitative method as its research approach. The study utilized a case study design conducted at MTs Nurussa’adah Teluk Rendah Tebo Ilir, examining a specific phenomenon related to students' difficulties in speaking English. Purposive sampling was used to select eighth-grade students as participants. Data were collected through observations and interviews to gather insights directly from the participants. Initial observations and teacher evaluations indicated that students at MTs Nurussa'adah faced challenges in expressing themselves in English, often resorting to their native language. Interviews further revealed various issues, including linguistic factors such as pronunciation, grammar, and vocabulary, as well as non-linguistic factors like motivation and the lack of English-speaking environments among peers